A model for the continuous quality improvement of the Sing With Us choir leaders. (1st September 2014) - Morris, Jessica Ruth; Dow, Rosie
Sing With Us is a network of fifteen research-led community choirs run weekly by the cancer charity Tenovus Cancer Care, as a form of support for people affected by cancer in Wales. This article discusses a model created by Tenovus Cancer Care to train and develop their team of eight community Choir Leaders (CLs). It explores the theoretical frameworks and methodology through which a system of continuous quality improvement has been developed for them, and looks specifically at the initial results of a first team assessment. This article will explore the idea that by professionalizing and valuing the roles of the CLs and the work they do, this will create a positive impact in the service that is provided. It will suggest that by implementing a process to ensure a quality leadership in a community choir setting, choristers will be more likely to have a richer experience on which they place high value and will be engaged for longer.